Design and Validation of Interactive Multimedia for Teaching The Human Transport System in Senior High School - Aryani, Ima; Agustina, Lina; Rahim, Auranur Priyanka; Sulistyowati, Erna (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Biology learning in high school requires multimedia to support the learning process. One of the multimedia developed is BioTranspezia. BioTranspezia is a technology-based media. Existing multimedia on the human transport system is generally static, less interactive, and not fully adapted to high school learning needs, so the development of innovative multimedia is still needed. The purpose of this study is to develop BioTranspezia multimedia as a biology learning medium for the human transport system. Methods: The research used a development research approach based on the Waterfall Process Model, with the stages of Communication, Planning, Modeling, Construction, and Deployment. This study focuses on assessing the feasibility of the developed multimedia and the perceptions of users, namely 2 teachers and 20 students (limited trial) and 36 (field trial). Results: BioTranspezia multimedia, validated by media experts, gets a score of 86% with the criterion of